2018
DOI: 10.1038/sdata.2018.270
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo probabilistic atlas of human thalamic nuclei based on diffusion- weighted magnetic resonance imaging

Abstract: The thalamic nuclei are involved in many neurodegenerative diseases and therefore, their identification is of key importance in numerous clinical treatments. Automated segmentation of thalamic subparts is currently achieved by exploring diffusion-weighted magnetic resonance imaging (DW-MRI), but in absence of such data, atlas-based segmentation can be used as an alternative. Currently, there is a limited number of available digital atlases of the thalamus. Moreover, all atlases are created using a few subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 33 publications
4
109
0
Order By: Relevance
“…Today, there are few available methods to automatically parcellate the thalamic nuclei based on local structural imaging features (Iglesias et al, 2018; Najdenovska et al, 2018; Su et al, 2019). To our knowledge, none of them has previously been used for the GM analysis in early psychosis or schizophrenia.…”
Section: Regions Of Interestmentioning
confidence: 99%
“…Today, there are few available methods to automatically parcellate the thalamic nuclei based on local structural imaging features (Iglesias et al, 2018; Najdenovska et al, 2018; Su et al, 2019). To our knowledge, none of them has previously been used for the GM analysis in early psychosis or schizophrenia.…”
Section: Regions Of Interestmentioning
confidence: 99%
“…Other networks involved in the effect of genotype included specific cortical areas involved in sustained attention tasks, such as the middle and inferior right frontal gyri, as well as in the functionally relevant subcortical structures of the anterior striatum/basal forebrain (Paus et al 1997(Paus et al , 2000. We also observed a selective involvement of the thalamus, consisting of a posterior portion (mainly localized to the lateral-posterior group and medial pulvinar) and the ventral-anterior portion (Najdenovska et al 2018). A structural connectivity study by Behrens et al (2003) has shown differential connectivity between thalamic nuclei and broad cortical areas.…”
Section: Discussionmentioning
confidence: 63%
“…In order to investigate whether this may be true also in humans, here we analyzed and characterized the anatomical and functional nature of thalamic portions recruited during the occurrence of human sleep slow waves ( Figure 4). First, we determined the percentage of activated voxels that fell within specific thalamic substructures identified using a probabilistic atlas of the human thalamus based on diffusion-weighted imaging (Najdenovska et al, 2018). For both the left and the right thalamus, we found that significant BOLD-signal changes especially involved medial nuclei located anteriorly, centrally and posteriorly (Figures 4D-E).…”
Section: Signal Change Regionmentioning
confidence: 99%
“…Specific analyses were performed to characterize the anatomical and functional nature of thalamic and cerebellar portions recruited during the occurrence of human sleep slow waves. First, anatomical atlases were used to determine the relative distribution (percentage) of activated voxels with respect to thalamic (probabilistic atlas based on diffusion-weighted imaging; Najdenovska et al, 2018) and cerebellar (SUIT atlas; Diedrichsen et al, 2011Diedrichsen et al, , 2009 subdivisions. Then, thalamic and cerebellar connectivity maps were generated and used to determine the preferential functional connectivity of activated voxels with respect to the seven canonical cortical networks defined on the basis of cortical intrinsic functional connectivity (Yeo et al, 2011): visual, somatomotor, dorsal attention, ventral attention, limbic, fronto-parietal and default mode.…”
Section: Eeg Data Preprocessing and Analysismentioning
confidence: 99%